Dissociating the Multiple Psychological Processes in Everyday Moral Decision-Making with the CAN Algorithm - Xie, Zhongju; Wu, Junhong; Wang, Xingyuan; Zheng, Ziyi; Liu, Chuanjun (Behavioral sciences, 2022)
In previous research frameworks, researchers used an everyday dilemma to test people’s altruistic versus egoistic inclination. However, there are at least three different psychological processes that could induce altruistic over egoistic decisions, i.e., stronger altruistic sensitivity, weaker egoistic sensitivity, and stronger overall action versus inaction preference. To dissociate these different psychological processes, we developed new materials and applied the CAN algorithm from traditional moral dilemma research in two studies. In Study 1, we designed scenarios varying with a 2 (egoistic/non-egoistic) × 2 (non-altruistic/altruistic) structure. Then, we recruited 209 participants to validate the scenarios and filtered six scene frameworks with 24 scenarios in total. In Study 2, we recruited 747 participants to judge whether they would conduct behavior that is simultaneously altruistic (or non-altruistic) and egoistic (or non-egoistic) in the filtered scenarios obtained from Study 1. They also filled in the Social Isolation Scale, Distress Disclosure Scale, and some other demographic information. As we dissociated the psychological processes using the CAN algorithm, significant correlations between social isolation and distress disclosure and three parameters (i.e., altruistic tendency, egoistic tendency, and overall action/inaction preference) underlying the altruistic choice were revealed to varying degrees. Other individual differences in the psychological processes in everyday moral decision-making were further demonstrated. Our study provided materials and methodological protocols to dissociate the multiple psychological processes in everyday moral decision-making. It promotes our insights on everyday moral decisions from a differential psychological processes perspective.